Influence of biological sex on neuroinflammatory dynamics in the aging brain - Müller, Ludmila; Di Benedetto, Svetlana; Müller, Viktor (Frontiers in Aging Neuroscience, 2025)
The aging brain undergoes complex neuroinflammatory changes that are increasingly recognized as contributing factors to the development and progression of neurodegenerative diseases. Emerging research reveals that biological sex profoundly shapes these neuroinflammatory dynamics, resulting in distinct trajectories of immune function, glial activity, and neural vulnerability in males and females. This mini-review focuses on recent advances in understanding the interplay of hormonal, genetic, and epigenetic factors that drive sex-specific differences of neuroinflammatory processes in aging brain. We begin by describing the hallmarks of neuroinflammation, including chronic activation of glial cells and the loss of inflammatory resolution. We provide a brief overview of age-related changes in microglial and astrocyte function, along with systemic influences such as immunosenescence, inflammaging, dysbiosis, and increased blood–brain barrier permeability. Building on this foundation, we examine sex-dependent differences in immune aging, CNS immune surveillance, and hormonal regulation of glial activity, particularly in the context of menopause and andropause. Particular attention is given to how these mechanisms drive sex-specific differences in the pathophysiology of neuroinflammation—a key contributor to many neurodegenerative diseases. Finally, we address key methodological challenges—such as the underrepresentation of females in preclinical models and limited sex-stratified clinical analyses—that constrain our understanding of sex-specific neuroinflammation in aging. By integrating sex as a critical biological variable and exploring systems-based approaches such as multilayer network models, this review highlights the importance of sex-informed research to better understand, prevent, and treat neuroinflammatory and neurodegenerative conditions in aging populations.